Analisis Faktor-Faktor yang Mempengaruhi Status Kemiskinan Rumah Tangga Provinsi Sumatera Barat - Rahmat Hidayat; Syamsul Amar (Universitas Negeri Padang, 2020)
This research was conducted to: (1) Determine the influence of gender on household poverty in West Sumatra. (2) Knowing the effect of education level on household poverty in West Sumatra. (3) Knowing the effect of Main Work on household poverty in West Sumatra (4) Knowing the effect of the number of household members on household poverty in West Sumatra. This research is descriptive and associative. The data used is the SUSENAS year sourced from the BPS of West Sumatra Province. The method uses Logistic Regression Analysis. The results of the study are: (1) Gender has a significant positive effect on the level of household poverty in West Sumatra, the head of the household is headed by a man. -men are more likely to be poor than households headed by women in West Sumatra. (2) The level of education has a significant negative effect on the level of poverty in West Sumatra, the increase in the level of education completed by the head of the family, the less likely it is for the household to become poor. (3) Main employment has a significant positive effect on poverty levels in West Sumatra. (4) The number of household members also has a significant positive effect on the level of household poverty in West Sumatra.